The Trachylepis (Squamata: Scincidae) of Angola: an integrative taxonomic review with the description of seven new species - Ceríaco, Luis M.P.; Marques, Mariana P.; Parrinha, Diogo; Tiutenko, Arthur; Weinell, Jeffrey I.; Butler, Brett O.; Bauer, Aaron M. (Bulletin of the American Museum of Natural History, 2024)
The genus Trachylepis is currently represented by 21 species in Angola, most of them part of nomenclaturally and taxonomically challenging species complexes. In this study we present an inte- grative taxonomic revision of the genus in Angola and describe seven new species: Trachylepis attenboroughi, sp. nov., Trachylepis bouri, sp. nov., Trachylepis hilariae, sp. nov., Trachylepis ovahelelo, sp. nov., Trachylepis suzanae, sp. nov., Trachylepis vunongue, sp. nov., and Trachylepis wilsoni, sp. nov. As result of our taxonomic revisions, 25 valid Trachylepis species are now confirmed from Angola. A phylogenetic analysis using a combination of mitochondrial (16S, ND2) and nuclear (RAG1) markers, as well as morphological data, supports the recognition of the new species. In addition, data support the revalidation of Trachylepis albopunctata (Bocage, 1867), Trachylepis notabilis (Peters, 1879), and Trachylepis ansorgii (Boulenger, 1907). We also provide a redefinition of Euprepes anchi- etae Bocage, 1866, which we synonymize with Trachylepis maculilabris (Gray, 1845). Given that the type material for Trachylepis albopunctata, T. angolensis, and T. anchietae has been lost or destroyed, we designate neotypes for the purpose of nomenclatural stability. The description of the new species and the revision and revalidation of previously described Angolan species contribute to a better understanding of the taxonomy and biogeography of the genus, as well as to the general biogeo- graphic patterns and evolution of the Angolan fauna.